2005
DOI: 10.1001/archopht.123.7.929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cataract Extraction on the Visual Fields of Patients With Glaucoma

Abstract: To investigate the effect of cataract extraction on the visual fields of patients with open-angle glaucoma. Methods: Patients in a prospective cohort study in a tertiary center underwent standard automated perimetry every 6 months. We compared the mean results of the 2 examinations immediately before and 2 examinations immediately after phacoemulsification cataract extraction and intraocular lens implant (effect analysis) and the mean results of the first 2 and last 2 examinations from 4 consecutive examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 10 publications
2
27
1
4
Order By: Relevance
“…Contradictory to our results, Stewart et al 3 and Carrillo et al 8 have reported MD to be unaffected by nuclear sclerotic cataracts. Possible reasons hypothesized for insignificant improvement in MD after cataract extraction are minimal cataract and advanced VF defects, with little scope for improvement.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Contradictory to our results, Stewart et al 3 and Carrillo et al 8 have reported MD to be unaffected by nuclear sclerotic cataracts. Possible reasons hypothesized for insignificant improvement in MD after cataract extraction are minimal cataract and advanced VF defects, with little scope for improvement.…”
Section: Discussionsupporting
confidence: 72%
“…These events are known to affect the VF parameters and confound the ability to detect glaucoma progression. [1][2][3][4][5][6][7][8][9] The recently introduced Guided Progression analysis (GPA) by the Humphrey Visual Field (HVF) Analyzer (Carl Zeiss Meditec, Inc. Dublin, CA) provides a new global index of the visual function of the eye called Visual Field Index (VFI). 10 The VFI is the aggregate percentage of visual function for a given field at each point where the visual thresholds are estimated.…”
mentioning
confidence: 99%
“…8,9,14,15 A limitation to this was the influence of media opacities like cataract on threshold sensitivities and MD. [16][17][18] Unlike MD, the new global index, VFI has been reported to be less affected by cataract. 2 We too have reported the effect of cataract on VFI previously, and found that nuclear cataracts had little effect on VFI while the posterior subcapsular cataracts tended to influence it.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Cataract development could mask the progressive loss of visual field in patients with glaucoma. [17][18][19][20][21] After cataract removal with IOL implantation, the IOL itself might confound the findings of common diagnostic tests such as perimetry. 7,22 Most IOLs used today block UV rays but do not filter violet and blue light to the same degree as the human crystalline lens 8,10 ; therefore, pseudophakic eyes are more vulnerable to harmful solar radiation.…”
Section: Discussionmentioning
confidence: 99%